Smart fare system for CNG - Alok, Shuvashish; Haque, Md. Enamul; Junayed, Rashidul Hasan; Tasmin, Rubaiya (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.